Contribuições dos acordos de parceria e contratos de prestação de serviços do IFSP para a inovação - Lima, Douglas Arcanjo de (2024)
The research investigates how the actions of the Federal Institute of São Paulo (IFSP) in innovation, carried out through partnership agreements and service provision contracts, contribute to socioeconomic and technological development, in alignment with the principles and challenges of the 2030 Agenda. The objective is to identify the elements present in the instruments signed by the IFSP innovation agency between 2018 and 2022, evaluating their role in strengthening the National System of Science, Technology and Innovation. Based on the Triple Helix theory, the research adopts a mixed methodological approach: the quantitative analysis was based on documentary data extracted from official publications, while the qualitative analysis involved interviews with four research coordinators and a representative of the innovation agency. The results indicated that most of the agreements and contracts were concentrated in the areas of Engineering and Information and Communication Technology, reflecting the institutional vocation and market demands. A predominance at the local and regional levels was observed, with most of the initiatives concentrated within the same intermediate region. Regarding the Sustainable Development Goals (SDGs), the instruments analyzed showed greater adherence to the economic pillar, with gaps in the social and environmental pillars. As a practical contribution, the study develops a checklist to assess the alignment of initiatives with the SDGs, offering an objective and subjective analysis tool. It is concluded that the IFSP plays a relevant role in promoting innovation, but faces challenges in diversifying areas of activity, in gender equity and in expanding initiatives aimed at the social and environmental pillars of the 2030 Agenda